The Students’ Ability on Comparison Degree in Irregular Form - Fatimah, Siti Nur (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2019)
The study is designed to investigate the students’ ability in using comparison degree on learning English especially in using irregular forms. To look their understanding about this matery the writer used method design descriptive design. Comparison degree was a compare between noun, people, and animal. Comparison degree has three type that was positive degree, comparative degree, and superlative degree. In taked the data of this study, the writer especially in taked data of comparative degree and superlative degree but just irregular forms. The sampling of data, the writer choose the students of the first grade at Madrasah Aliyah Muhammadiyah Aimas of number 20 person. The writer used written test as tools to take the data that was multiple-choise of number eighteen comparative degree and seventeen to superlative degree. Before doing research, the writer explains about comparison degree in irregular forms to the students and then the writer given tast about comparative degree in irregular forms to the students. First step done the author was giving material of paper to students about comparison degree in irregular form and both steps given the students exercise about matery had given as multiple-chooise. After that, exercise correct and analyze. By this test given by the author getting the data for her research. From 12 students of first grade at Madrasah Aliyah Muhammadiyah Aimas got score, to comparative degree in worse = 69%, better = 62%, farther = 85%, less = 69%, more = 96%, elder = 7,7%. Commonly, their ability can be seen based on the score of test, in which they got their mean of score of test was 47%. The writer can explain that the students of the first grade at Madrasah Aliyah Muhammadiyah Aimas yet understand about comparative degree, their ability was still including in bad category, and superlative degree specifically on worst = 65%, best = 50%, farthest = 23%, least = 8%, most = 31%, Eldest = 89%. In overall, can be seen their mean score of superlative degree = 32%. It means that their ability in superlative degree was very bad. By this result, the writer found that the students understanding on superlative degree was still very minus.